Impacts of Bacillus-based biotics and an enzyme cocktail on growth performance, immunity, and gut pathogenic microorganisms of nursery pigs under commercial conditions - Koo, Seong-Min; Lee, Jae-Hyeok; Oh, Sang-Hyon; Jang, Jae-Cheol (Frontiers in Veterinary Science, 2025)
IntroductionThe prohibition of antibiotics in animal feed has increased interest in alternatives, such as phytogenic compounds, pro- and prebiotics, organic acids, and exogenous enzymes. Among these, Bacillus-based biotics and enzyme cocktail are the most commonly used feed additives. However, their effects on growth performance, immunity, and gut health in nursery pigs, as well as their interactions with pathogens under commercial conditions, remain unclear. This study investigated the impact of these additives on growth performance, immunity, and pathogenic microorganisms in the gut under commercial conditions.Material and methodsTwo hundred nursery pigs were assigned to one of five dietary treatments: (1) CON: a basal corn-soybean meal diet, (2) A: basal diet with 0.05% probiotics, (3) B: basal diet with 0.1% synbiotics containing one strain, (4) C: basal diet with 0.1% synbiotics containing two strains, and (5) D: basal diet with 0.1% enzyme cocktail.ResultsThe growth performance did not show significant differences according to the feed additives. In terms of immunity, B treatment increased immunoglobulin M levels, while D treatment increased immunoglobulin A levels during weeks 0–2 (p < 0.01). Additionally, both B and D treatments decreased Mycoplasma spp. in the gut, as indicated by log fold change (LFC) values of −1.571 and −1.529, respectively.Conclusion and implicationsTherefore, this study highlights the potential of Bacillus-based biotics and enzyme cocktail as practical alternatives for reducing pathogenic microorganisms such as Mycoplasma spp. and improving immunity in nursery pigs under commercial conditions.